Open-school models for crisis-affected adolescents: Findings from a World Bank Feasibility study - Karen Ferreira-Meyers; Frederico Carvalho; Sarah Kleinmann; Maria Barron Rodriguez (Perspectives in Education)
Recently, the World Bank (2023–2024) conducted a comprehensive feasibility study to assess the potential of implementing open school models for adolescents aged 12 to 16 from nomadic, refugee and internally displaced populations from countries on the Fragility, Conflict and Violence (FCV) list, with particular focus on the following five countries from the Sahel region: Burkina Faso, Mauritania, Chad, Mali and Niger. The study employed a mixedmethods approach combining desktop research and quantitative assessments to gather data from diverse contexts, including remote and conflict-affected areas while exploring appropriate technological solutions and Artificial Intelligence (AI) applications. The findings present a compelling case for adopting and scaling open-school models to provide inclusive educational opportunities for crisis-affected adolescents, highlighting that participatory, learner-centred approaches foster ownership and motivation among learners. At the same time, culturally relevant curricula contribute to increased retention and improved learning outcomes. The study identified key implementation factors, including community engagement, comprehensive teacher training, contextually relevant learning materials and strategies for overcoming logistical and infrastructural barriers in remote areas, demonstrating how these models could help FCV countries progress toward Sustainable Development Goal 4 (SDG 4) by addressing the significant barriers marginal groups face in accessing traditional education systems.